Fiction’s strategies of evidence and their cultural significance: The scientist as writer (ENTHYMEMA, 2014)
This article analyses the popular novel Sannikov’s land (published in 1926) by the famous Russian and Soviet geologist Vladimir A. Obruchev (1863–1956). It asks how scientific discourse on the one hand, and literary, fictional discourse on the other interact in this text that tells the story of the discovery of an Arctic island, which a Russian merchant had asserted to have seen, but the existence of which never could be affirmed. Basing his novel exclusively on well-founded scien- tific (geological as well as anthropological) hypotheses, Obruchev polemizes with a whole range of earlier texts from J. Verne to K. Hloucha. Unfolding the story of the Russian expedition, Obruchev pursues the aim (1) to deconstruct the utopian myth of a paradise on earth beyond the Arctic ice in its countless varieties; (2) to show that ancient myths—like the myth of the ex- istence of warm islands in the Arctic—are a form of protoscientific insight that should be taken seriously by modern science and transformed into scientific knowledge; and (3) to suggest that the Arctic islands—really existing, supposed to exist or be doomed—from a geological point of view belong to the Siberian mainland and therefore to Russian/Soviet territory.